TREN PENELITIAN LITERASI LINGKUNGAN PADA PENDIDIKAN DASAR DAN IMPLIKASINYA TERHADAP PEMBANGUNAN BERKELANJUTAN: SYSTEMATIC LITERATURE REVIEW DAN BIBLIOMETRIC ANALYSIS - Ainur Rofiqi; Intan Sari Rufiana; Radeni Sukma Indra Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Environmental education has evolved from raising basic awareness to integrating complex sustainability concepts and interdisciplinary skills in the curriculum since the 20th century. This study is a Systematic Literature Review and Bibliometric Analysis which aims to map research trends, keyword networks, and implications of environmental literacy research in basic education on the achievement of sustainable development goals. A study was conducted on 21 scientific articles that have gone through the inclusion and exclusion stages. The results of the study show that there is a fluctuating trend in environmental literacy research in primary education, but it tends to increase in 2024 and 2025. The keyword